Direct oral anticoagulants for the treatment of cancer-associated venous thromboembolism - Voigtlaender, Minna; Langer, Florian (Hämostaseologie, 2017)
Cancer patients with venous thromboembolism (VTE) are at increased risk for both bleeding and VTE recurrence. Anticoagulation with low-molecular-weight heparin (LMWH) is the standard of care during the initial and longterm treatment phase (i.e. during the first 3 – 6 months of therapy) based on its overall beneficial safety and efficacy profile compared to vitamin K antagonists (VKAs). The direct oral anticoagulants (DOACs) rivaroxaban, apixaban, edoxaban, and dabigatran are approved for the treatment of acute VTE, and the combined six phase-3 trials have included > 1500 patients with active cancer, as defined by variable selection criteria. Subgroup analyses of these patients, either pooled or separately reported, suggest that DOACs could be a safe and efficacious alternative to VKA therapy for the treatment of cancer-associated VTE. However, the populations of cancer patients included in the DOAC and LMWH trials are not comparable with regard to mortality and VTE risk, and no specific data from direct head-to-head comparisons of DOACs with LMWHs are currently available. The use of DOACs for the management of VTE in cancer is thus not recommended by clinical practice guidelines.
Keywords: malignancy; venous thrombosis; pulmonary embolism; heparins